Promoting Literacy And Education In Marginaized Communities - Kadek Feni Aryati (Jurnal SOLMA, 2023)
Background: Education and literacy are the main foundations for building an inclusive and sustainable society. This community service aims to promote literacy and education in marginalized communities. Method: The method used in this service is asset based community development. ABCD aims to mobilize the potential and strength of the community to improve their own quality of life. The location of this service is in Bali. Data collection techniques by identifying the resources, expertise, and assets that exist in the community. These can be individual skills, local organizations, untapped land, or cultural and historical forces. Data analysis by encouraging collaboration between residents, local organizations and other related parties (Public participation). Results: Promoting literacy and education in underserved communities in Bali has a profoundly positive impact. These initiatives empower individuals by granting them access to knowledge and skills that foster a deeper comprehension of the world and lead to more informed decision-making. Beyond simply expanding job prospects, literacy and education also act as a bulwark against poverty for future generations. Moreover, they enhance awareness of health, hygiene, and healthy lifestyles, simultaneously diminishing social and economic disparities.